Methodology of optimal distribution of single-phase electric consumers in power supply systems by the criterion of reduction of additional losses caused by load asymmetry and non-sinusoidality - A. A. Pesterev; S. S. Kostinskiy; N. D. Narakidze (Вестник Северо-Кавказского федерального университета)
Introduction. The increase in the number and installed capacity of loads with nonlinear and unbalanced characteristics in modern power supply systems leads to deterioration in power quality and additional power losses. In this article, the authors address the pertinent task of distributing single-phase loads within the electrical system of an office building to assess the total share of additional losses resulting from asymmetry and non-sinusoidal waveforms in the overall structure of losses in the 0.4 kV distribution network. Goal. The study aims to develop a technique based on an algorithm for optimal distribution of singlephase loads over phases L1, L2, and L3 of the power supply system during their dynamic operation using a genetic algorithm to minimize additional losses in electrical equipment caused by asymmetry and non-sinusoidal waveforms.Materials and methods. A digital parameter meter for single-phase electrical receivers has been developed to collect initial data from office electrical receivers in the form of arrays with instantaneous values of supply voltage and current. In the developed algorithm, the target function utilizes exponential loss values in the unbalanced mode over losses in the balanced mode, as well as additional losses due to higher harmonic components. Results and discussion. The results of the assessment of additional losses calculated using the proposed methodology are presented for the optimal distribution of single-phase loads in an office building, taking into account their operational modes throughout the working day. The efficiency of the developed methodology application at the stage of power supply systems design with the traditionally used approach has been estimated by comparing the values of additional power losses during the distribution of single-phase electric consumers in static mode (39,9 % more efficient) and in dynamic mode (77,1 % more efficient).Conclusion. The developed methodology enabled the creation of a fundamentally new technical solution that can be implemented in both existing and newly designed power supply systems, allowing for minimization of losses in electrical equipment by reducing additional losses caused by asymmetry and non-sinusoidality.